2007
DOI: 10.1021/bi700425y
|View full text |Cite
|
Sign up to set email alerts
|

Human p53 Is Inhibited by Glutathionylation of Cysteines Present in the Proximal DNA-Binding Domain during Oxidative Stress,

Abstract: The cellular mechanisms that modulate the redox state of p53 tumor suppressor remain unclear, although its DNA binding function is known to be strongly inhibited by oxidative and nitrosative stresses. We show that human p53 is subjected to a new and reversible posttranslational modification, namely, S-glutathionylation in stressed states, including DNA damage. First, a rapid and direct incorporation of biotinylated GSH or GSSG into the purified recombinant p53 protein was observed. The modified p53 had a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 61 publications
(130 reference statements)
8
164
1
Order By: Relevance
“…Under mild oxidative stress, protein glutathionylation was shown to regulate the functions of multiple proteins. 23,31 Here, we showed that the antiapoptotic protein MCL1 is a novel substrate of glutathionylation in CLL cells, and that such glutathionylation regulates its stability. Removal of glutathionylation by the glutathione-depleting agent PEITC rendered MCL1 susceptible to rapid proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Under mild oxidative stress, protein glutathionylation was shown to regulate the functions of multiple proteins. 23,31 Here, we showed that the antiapoptotic protein MCL1 is a novel substrate of glutathionylation in CLL cells, and that such glutathionylation regulates its stability. Removal of glutathionylation by the glutathione-depleting agent PEITC rendered MCL1 susceptible to rapid proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that the depletion of glutathione might play a role in MCL1 cleavage. Because glutathionylation of certain proteins may affect their functions and stability, 23,31 we speculated that MCL1 may be a target of glutathionylation, and its glutathionylation status might affect susceptibility to caspase-cleavage. To test the possibility, we first examined whether in vitro glutathionylation of MCL1 could protect it from cleavage by caspase-3.…”
Section: Induction Of Rapid Degradation Of the Antiapoptotic Protein mentioning
confidence: 99%
“…This is in conflict with both their X-ray crystallography data and the top-down FTICR MS results described here. Intriguingly, Velu et al [46] also concluded that Cys141 is the most reactive cysteine residue in p53, after using a bottom-up MS approach to investigate cysteine alkylation. Cys141 has a solvent accessibility value of zero, and the X-ray crystal structure of the p53 core domain shows that it is buried within two sides of the β-sheet sandwich (see Table 1 and Fig.…”
Section: Preferential Alkylation Of Cys182 and Cys277mentioning
confidence: 99%
“…Several signaling proteins have been shown to undergo glutathionylation, including PTPs and transcription factors (36,63,(77)(78)(79)(80). Although the mechanism by which glutathionylation occurs is not agreed upon, this process has been shown occur in vivo in relevant cell types (81)(82)(83)(84)(85)(86). Although glutathionylation of PTP1B can be achieved in vitro with the purified enzyme through oxidation by H 2 O 2 and addition of GSH (through the sulfenic acid and sulfenyl-amide as described above) (26) (27) or by addition of a very high concentration of GSSG (63), it is not known if glutathionylation occurs enzymatically or non-enzymatically in vivo and kinetic considerations clearly argue against the latter (87).…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 99%